USAGE OF CREATIVE ART PROCESS IN CAREER PREPARATION FOR A STUDENT WITH LOW VISION AND MULTIPLE DISABILITIES - Boonmak, Pornrat; Tongsookdee, Ratchaneekorn; Leosiripong, Pikul; Vittayakorn , Soisuda (Journal of Buddhist Anthropology, 2022)
The objective of this research article were to examine the usage of creative art process in career preparation for students with low vision and multiple disabilities (MD) in School for Disabilities, Chiang Mai Province. This research was the mixed methods research. A case study was chosen using Purposive Sampling with four conditions: 1) Being a student with low vision and MD studying at the School for Disabilities, 2) Being participated in vocational programmed group of MD students, 3) Being capable of and interested in art works and 4) Over 15 years old. Based on these conditions, the selected case study is a 20 yrs. female student with an ID card for persons with disabilities type 1.2.5 (low vision, hearing impairment, and deaf). The case study can see with the aid of eye glasses and communicate through sign language. Research tools applied were 1) Three individual implementation plans (IIPs), 2) An evaluation form assessing career preparation and 3) An evaluation form assessing printing artwork on a canvas bag. The IIPs were taught six times each, (18 times totally). Data were analyzed in terms of mode, quality levels, and descriptive analysis. The results revealed that 1) The career preparation in terms of 1.1) insight, 1.2) working skills, and 1.3) pride of the artwork, indicated that the mode is at level 3 implying good quality. 2) The piece of artwork on a canvas bag produced by the art - making process showed that 2.1) creativity, 2.2) artwork based on composition principle, 2.3) neatness, and 2.4) attention on the active, indicated that the mode is at level 2 implying average quality. The case study created the artwork correctly according to composition principle. However, the case study was self - practiced from last time product memory. There were no modifications or additions that expressed more clearly about exotic creativity.